Leadership enhancing the lessons of experience - Hughes, Richard L. (McGraw-Hill, 2012)
Covers specific leadership skills and qualities. Drawing upon three different types of literature - empirical studies; interesting anecdotes, stories and findings; and, leadership skills - this text helps students apply theory and research to their real-life experiences.